Effects of the improved application of Bacillus halotolerans on the microbial community and volatile components of high-temperature daqu - Cheng, Wei; Guo, Lele; Xue, Xijia; Jiang, Chao; Chang, Qiang; Chen, Xuefeng (Frontiers in Microbiology, 2025)
IntroductionStudies found similar dynamics in the physicochemical properties, microbial communities, and flavor compounds during fortified daqu fermentation. However, there have been few studies on the application of B. halotolerans to fortified high-temperature daqu (HTD), and its effects on the physicochemical parameters, microbial communities, and volatile components (VOCs) of fortified HTD are unclear.MethodsDuring the fermentation of B. halotolerans fortified HTD, the amplicon sequencing was used to analyze the microbial community, headspace solid-phase microextraction-gas chromatography–mass spectrometry (HS-SPME-GC–MS) was used to analyze the VOCs, and the relationships between physicochemical parameters, dominant microbial communities, and VOCs were analyzed based on redundancy analysis (RDA).ResultsAfter fortification with B. halotolerans, the acidity, saccharification power, and fermentation power of fortified HTD were higher than those of traditional HTD. The fortification with B. halotolerans had a significant effect on bacterial diversity, with an increase in the relative abundance of Bacillu. For fortified HTD, the contents of certain VOCs, such as alcohols and esters, were improved compared to their contents in traditional HTD at the end of daqu fermentation. Further, after fortification with B. halotolerans, the effects of physicochemical properties on the composition and function of bacterial flora were greater than those on fungal flora, while fungal flora had a greater impact than bacterial flora on VOCs.DiscussionThe fortification with B. halotolerans controlled microbial metabolism by altering the composition and abundance of certain microorganisms and promoting the production of specific VOCs, which also influenced the physicochemical properties of HTD. These results provide a basis and new insights for the application of functional strains in daqu fermentation.